2009
DOI: 10.1038/jp.2009.150
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes associated with planned vaginal versus planned primary cesarean delivery

Abstract: Objective: To determine whether planned route of delivery leads to differences in neonatal morbidity.Study Design: Analysis was based on planned route of delivery, not actual route of delivery. A total of 4048 subjects were divided into two groups: planned vaginal delivery and planned cesarean delivery. Primary outcomes were neonatal intensive care unit (NICU) admission, respiratory morbidity and neurologic morbidity.Result: There were 3868 planned vaginal and 180 planned cesarean deliveries. Planned vaginal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 18 publications
4
23
0
4
Order By: Relevance
“…Similar results are reported in the international literature, where midwife-led care is associated with fewer obstetric interventions than other models of care [14]. Although it is clear that adequate access to obstetric interventions such as emergency caesarean delivery can save the life of both the mother and infant [15], [16], high rates of operative delivery, particularly rates above 15%, may result in poorer maternal and infant outcomes for the current or subsequent births [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]. With the rising caesarean section rates during the last few decades in the developed world, adverse outcomes following birth are gaining greater attention [31], [32], [33], [34], [35].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results are reported in the international literature, where midwife-led care is associated with fewer obstetric interventions than other models of care [14]. Although it is clear that adequate access to obstetric interventions such as emergency caesarean delivery can save the life of both the mother and infant [15], [16], high rates of operative delivery, particularly rates above 15%, may result in poorer maternal and infant outcomes for the current or subsequent births [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]. With the rising caesarean section rates during the last few decades in the developed world, adverse outcomes following birth are gaining greater attention [31], [32], [33], [34], [35].…”
Section: Discussionsupporting
confidence: 71%
“…However, it appears clear from other studies that increases in maternal or foetal risk indicating the need for operative delivery are not a major factor [39], [40]. Due to the increased risk of injury and morbidity in the mother and infant following high rates of operative deliveries [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], it seems clear that although the LHC policy may have been successful in achieving the government’s aim of relieving pressure on public hospitals [7], it may not have been beneficial for quality obstetric care in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] For example, studies have reported that children born by cesarean delivery may have increased rates of respiratory illness in their first year of life 5,7,8 and beyond, 9,10 and relationships have also been described with diabetes 11 and child overweight and obesity. 12,13 Notwithstanding these potential adverse associations, children born by cesarean delivery are usually healthy, and it is important to recognize that many factors influence child health other than mode of birth.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Apgar scores at 5 minutes have reported to be better in healthy infants born by elective caesarean than in other infants [22] and our results indicated that privately insured women were almost twice as likely as publicly insured women to deliver by pre-labour caesarean section following a preterm birth. However, adjusting for mode of delivery did not change our results and it is therefore more likely that the higher risk of low Apgar score in publicly insured women in public hospitals is either due to residual confounding in our data or practise differences between public and private hospitals in Western Australia.…”
Section: Discussionmentioning
confidence: 52%